QURTHUBI’S VIEW: CONSUMPTION BEHAVIOUR IN SURAH AL-A’RAF VERSE 31 - Wahyu Syarvina; Reza Febrian; Azhari Akmal Tarigan; Yenni Samri Juliati Nasution (IAIN Lhokseumawe, 2022)
Consumption activity in Islamic teachings is one of human economic activities that aims to increase worship and faith in Allah SWT in order to get peace, victory and prosperity in the hereafter (falah), either by spending money or income for his own needs or for good deeds for others. In the view of conventional economics, consumption activities are closely related to maximizing satisfaction (utility). In this study, the data used is qualitative data with the data source used in the book of Tafsir Al-Qurthubi. Consumption behavior in Qurthubi's view is that consumption is limited to meeting needs not desires, the purpose of consumption is to maximize benefits not just satisfaction, eating and drinking that is lawful and good, should not be excessive in consumption but is more recommended to be proportionate according to each individual's needs. as a form of health care.